Magnetotail shape at lunar distances: ARTEMIS observations - Akay, Iklim Gencturk; Kaymaz, Zerefsan; Sibeck, David G. (IEEE, 2013)
The magnetotail has been one of the least studied magnetic regions of the Earth's magnetosphere compared to the other near Earth both dayside and nightside magnetospheric regions owing to the limited number of spacecraft observations. Since 2011, ARTEMIS spacecraft, which consists of twin spacecraft, give an opportunity to study the magnetotail. Both ARTEMIS spacecraft have a trajectory around the Moon but at the same time they sample the magnetospheric regions of the Earth at -60 Re as the Moon moves around the Earth. With the state-of-the-art instruments, ARTEMIS probes perform the first systematic, two-point observations of the mid-to-distant tail and allow us to determine its field and plasma structure, field geometry, and their solar wind dependence. Thus, it helps us to understand how the tail dynamics work and controlled at this distance. In this study, we use magnetopause crossings to investigate the shape of the magnetotail, structure of the tail magnetopause, and its response to the solar wind plasma and IMF at this distance. We determine 68 magnetopause crossings and plot them at yz- and xR-planes. We test analytical magnetopause models for our magnetopause crossings and point out the differences. We compare our results with those of previous studies.